MAINTENANCE DECISION MAKING MODEL USING MULTIPLE CRITERIA ANALYSIS FOR SMALL AND MEDIUM INDUSTRIES - M.A., Burhanuddin; A.R., Ahmad; M.I., Desa (FSKSM, UTM, 2007)
In small and medium industries (SMI), there are less number of machines use, which are always grouped together in serial lines. Well organized of these machines maintenance structure will ensure the effectiveness of the entire production lines. Their maintenance data should be stored to process and subsequently transform them into a useful knowledge for decision making. In order to increase the effectiveness of the machines in the production lines, we have studied some decision support models in maintenance area. Choosing the model and optimizing maintenance strategies is the formost importance in maintenance management. We have written a paper to identify the strategies for the machines based on 2 factors, i.e. downtime and frequency of machines failures with multiple criterions using decision making grid (DMG) model. In this paper, we use the results obtained from the maintenance strategies implementation in one of the SMI in Malaysia. We collected raw data for the whole period of 2004 and 2005 for analysis using DMG model. We gave few recommendations to the maintenance crew after analyzing the dataset. In 2006, we collected the data again and compare the result after the implementation of those strategies.